2020
DOI: 10.48550/arxiv.2009.04263
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Real-World Snapshots vs. Theory: Questioning the t-Probing Security Model

Thilo Krachenfels,
Fatemeh Ganji,
Amir Moradi
et al.

Abstract: Due to its sound theoretical basis and practical efficiency, masking has become the most prominent countermeasure to protect cryptographic implementations against physical sidechannel attacks (SCAs). The core idea of masking is to randomly split every sensitive intermediate variable during computation into at least t+1 shares, where t denotes the maximum number of shares that are allowed to be observed by an adversary without learning any sensitive information. In other words, it is assumed that the adversary … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The same holds true for application keys after they have been decrypted. Previous work has shown that sophisticated non-and semiinvasive FA tools are capable of extracting logic states from CMOS logic gates [16] and memory cells [8,10,11]. These techniques typically produce an image (i.e., activity map or response image) which contains information about the logic state of the area of interest.…”
Section: Root Key Rot Socmentioning
confidence: 99%
See 4 more Smart Citations
“…The same holds true for application keys after they have been decrypted. Previous work has shown that sophisticated non-and semiinvasive FA tools are capable of extracting logic states from CMOS logic gates [16] and memory cells [8,10,11]. These techniques typically produce an image (i.e., activity map or response image) which contains information about the logic state of the area of interest.…”
Section: Root Key Rot Socmentioning
confidence: 99%
“…Yet, extracting the actual memory content from these images can be a challenging task, even if the chip's layout is known, or at least understood to a certain degree. Although tools like SAT solvers [11] and image recognition techniques can aid the localization of the key, much prior knowledge of the memory cell's design, its geometry, and its exact location is required. Therefore, a potential attacker might be highly motivated to reduce the effort for extracting keys from the images.…”
Section: Root Key Rot Socmentioning
confidence: 99%
See 3 more Smart Citations